2018
DOI: 10.3892/ol.2018.9332
|View full text |Cite
|
Sign up to set email alerts
|

A dosimetric study on radiation‑induced hypothyroidism following intensity‑modulated radiotherapy in patients with nasopharyngeal carcinoma

Abstract: Abstract. The objective of the present study was to investigate the association between thyroid gland-dosimetric parameters and hypothyroidism induced by intensity-modulated radiotherapy in patients with nasopharyngeal carcinoma (NPC). A total of 52 patients with NPC treated in the Department of Radiation Oncology of The Affiliated Hospital of Xuzhou Medical University, from May 2008 to December 2016 were retrospectively enrolled in the present study and divided into two groups based on thyroid function: The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 28 publications
(35 reference statements)
4
26
1
Order By: Relevance
“…Huang [18] reported that TSH and FT 4 were correlated with the pituitary volume receiving doses of > 55 Gy. However, a recent study showed that the Dmean, V 30 , V 40 , V 50 and V 55 of the pituitary gland indicated no significant differences between the euthyroid and hypothyroid groups (P > 0.05) [28]. Similarly, we did not find a correlation for pituitary dose and radiationinduced damage to thyroid function.…”
Section: Hypothyroidism and Pituitary Dosecontrasting
confidence: 91%
“…Huang [18] reported that TSH and FT 4 were correlated with the pituitary volume receiving doses of > 55 Gy. However, a recent study showed that the Dmean, V 30 , V 40 , V 50 and V 55 of the pituitary gland indicated no significant differences between the euthyroid and hypothyroid groups (P > 0.05) [28]. Similarly, we did not find a correlation for pituitary dose and radiationinduced damage to thyroid function.…”
Section: Hypothyroidism and Pituitary Dosecontrasting
confidence: 91%
“…Recent studies on patients with Hodgkin’s lymphoma, breast cancer and head and neck cancer, proposed different dose-volumetric parameters for the prediction of HT development, mostly including the proportion of thyroid volume receiving some X dose (VX). In these studies, the defined VX threshold parameters ranged from V10 to V50 2,4,11,17, 18, 19, 20. However, the proposed proportion of thyroid volume that could receive VX dose was different among studies, making it difficult to draw strong conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…as a useful guideline to avoid HT 12. In the paper from Xu, the threshold level of V50 was set to 54.5% 20. When all these results are analysed collectively, it can be concluded that the rate of HT is small in patients receiving < 50 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy might have been caused by the research endpoints not including central hypothyroidism. Other studies have found no correlation between T stage and the incidence of hypothyroidism [43]. Fujiwara et al [37] analyzed 116 patients with head and neck cancer who received 3D-CRT, and univariate analysis showed that the incidence of hypothyroidism was significantly higher in the positive cervical lymph node group.…”
Section: Clinical Stagementioning
confidence: 95%